Differentiated Learning Management in Improving Children's Cognitive Development and Creativity in Kindergarten - Ratnawati, Endang; Sobri, Ahmad Yusuf; Arifin, Imron (Education and Talent Development Center Indonesia (ETDC Indonesia), 2025)
The implementation of the Independent Curriculum at the Early Childhood Education level faces challenges in accommodating the diverse characteristics and unique learning rates of children. This study aims to explain and analyze differentiated learning management and its impact on the cognitive development and creativity of early childhood at the Kindergarten Model in Malang City. The research method used was a qualitative approach with a case study design. The research subjects included the principal and teachers, with data collection techniques using participatory observation, in-depth interviews, and documentation studies. Thematic data analysis was performed via data reduction, data presentation, and conclusion formulation, with its validity assessed through source and method triangulation. The results indicated that differentiated learning was managed systematically through the stages of planning, implementation, and assessment. Differentiation was applied to aspects of content, process, product, and learning environment by adjusting the level of readiness, interests, and learning profiles of children. This implementation has been proven to have a significant positive impact on cognitive development, especially in logical thinking, pre-mathematics, and simple problem-solving skills. In addition, children's creativity increased through meaningful play activities, free exploration, and the use of diverse media such as loose parts. This research provides a practical contribution as a reference for effective implementation strategies for the Independent Curriculum in Early Childhood Education units to create inclusive and child-centered learning.